Business Dispute Resolution Through Arbitration: Effectiveness and Challenges in Practice - Pajow, Roof Oudy (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2025)
This study aims to analyze the effectiveness and challenges of arbitration as a mechanism for resolving business disputes in Indonesia The research focuses on evaluating the effectiveness of arbitration in terms of time and cost identifying institutional and regulatory challenges and analyzing factors influencing the success of business arbitration The research method uses a qualitative approach with literature study techniques that examine various academic literature sources laws and regulations and official documents of arbitration institutions Data analysis was conducted through content analysis and thematic analysis to identify patterns and categories of findings The results show that arbitration has significant advantages in time efficiency 6 12 months vs 2 5 years of litigation and cost effectiveness for large value disputes but faces challenges in geographical accessibility standardization of service quality and inconsistent legal interpretation Key factors for arbitration success include the quality of arbitration clause drafting arbitrator competence commitment of the parties and support from the legal system The study concludes that although arbitration offers an effective alternative for resolving business disputes optimizing its effectiveness requires institutional reform regulatory harmonization and increased human resource capacity within the Indonesian arbitration ecosystem < p>